Calculation:

Consider, the equation, \(\displaystyle{3}{y}+{2.5}{x}—{3.4}={0}\),

To compute x-intercept, put \(\displaystyle{y}={0}\),

\(\displaystyle{3}\cdot{0}+{2.5}{x}-{3.4}={0}\)

\(\displaystyle{2.5}{x}-{3.4}+{3.4}={0}+{3.4}\)

\(\displaystyle{\frac{{{2.5}}}{{{2.5}}}}{x}={\frac{{{3.4}}}{{{2.5}}}}\)

\(\displaystyle{x}={1.36}\)

So, the x-intercept is (1.36, 0).

To compute y -intercept, put \(\displaystyle{x}={0}\),

\(\displaystyle{3}{y}+{2.5}\times{0}-{3.4}={0}\)

\(\displaystyle{\frac{{{3}{y}}}{{{3}}}}={\frac{{{3.4}}}{{{3}}}}\)

\(\displaystyle{y}={\frac{{{3.4}}}{{{3}}}}\)

\(\displaystyle{y}={1.13}\)

So, the y -intercept is (0, 1.13).

Hence, the x and y-intercepts of \(\displaystyle{3}{y}+{2.5}{x}-{3.4}={0}\) are (1.36,0) and (0,1.13), respectively.

Consider, the equation, \(\displaystyle{3}{y}+{2.5}{x}—{3.4}={0}\),

To compute x-intercept, put \(\displaystyle{y}={0}\),

\(\displaystyle{3}\cdot{0}+{2.5}{x}-{3.4}={0}\)

\(\displaystyle{2.5}{x}-{3.4}+{3.4}={0}+{3.4}\)

\(\displaystyle{\frac{{{2.5}}}{{{2.5}}}}{x}={\frac{{{3.4}}}{{{2.5}}}}\)

\(\displaystyle{x}={1.36}\)

So, the x-intercept is (1.36, 0).

To compute y -intercept, put \(\displaystyle{x}={0}\),

\(\displaystyle{3}{y}+{2.5}\times{0}-{3.4}={0}\)

\(\displaystyle{\frac{{{3}{y}}}{{{3}}}}={\frac{{{3.4}}}{{{3}}}}\)

\(\displaystyle{y}={\frac{{{3.4}}}{{{3}}}}\)

\(\displaystyle{y}={1.13}\)

So, the y -intercept is (0, 1.13).

Hence, the x and y-intercepts of \(\displaystyle{3}{y}+{2.5}{x}-{3.4}={0}\) are (1.36,0) and (0,1.13), respectively.